Transfer‐Tattoo‐Like Cell‐Sheet Delivery Induced by Interfacial Cell Migration. Issue 4 (30th September 2022) - Park, Ju An; Youm, Yejin; Lee, Hwa‐Rim; Lee, Yongwoo; Barron, Sarah L.; Kwak, Taejeong; Park, Gyu Tae; Song, Young‐Cheol; Owens, Róisín M.; Kim, Jae Ho; Jung, Sungjune
Abstract: A direct transfer of a cell sheet from a culture surface to a target tissue is introduced. Commercially available, flexible parylene is used as the culture surface, and it is proposed that the UV‐treated parylene offers adequate and intermediate levels of cell adhesiveness for both the stable cell attachment during culture and for the efficient cell transfer to a target surface. The versatility of this cell‐transfer process is demonstrated with various cell types, including MRC‐5, HDFn, HULEC‐5a, MC3T3‐E1, A549, C2C12 cells, and MDCK‐II cells. The novel cell‐sheet engineering is based on a mechanism of interfacial cell migration between two surfaces with different adhesion preferences. Monitoring of cytoskeletal dynamics and drug treatments during the cell‐transfer process reveals that the interfacial cell migration occurs by utilizing the existing transmembrane proteins on the cell surface to bind to the targeted surface. The re‐establishment and reversal of cell polarity after the transfer process are also identified. Its unique capabilities of 3D multilayer stacking, freeform design, and curved surface application are demonstrated. Finally, the therapeutic potential of the cell‐sheet delivery system is demonstrated by applying it to cutaneous wound healing and skin‐tissue regeneration in mice models. Abstract : The development of a transfer‐tattoo‐like cell‐sheet delivery platform is described, based on interfacial cell migration. The use of a commercially available flexible parylene film facilitates the manipulation of cell sheets and the creation of freeform designs. The efficacy of a multilayered cell‐sheet skin substitute in promoting re‐epithelialization and re‐vascularization of wounds in mouse models is demonstrated.